Listening with your eyes: Multimodal approaches to art appreciation in primary school - lvalue lvalue; Ruth Breeze (Universitat Jaume I. Department of English Studies, 2018)
Author/s Ruth Breeze Instituto Cultura y Sociedad, Universidad de Navarra, Spain   ABSTRACT Fine arts offer opportunities for multimodal approaches in education. Museums and galleries are now aware of their social role, and provide outreach activities designed to bring an understanding of art to a wider public. Their websites offer educational material for school children, showing how artistic knowledge and sensitivity can be cultivated with young age groups. However, little attention has been paid to such didactic material by discourse analysts interested in multimodality. This paper builds on Swales's (2016) article on the genre of the single image account (SIA), which centres on texts about famous paintings written by experts for a general readership. Here, I focus on SIAs for didactic purposes, examining pedagogical resources on the National Gallery's website. Accessible SIAs are combined with suggestions to enhance primary school pupils' learning through creative activities across a variety of modes. Guidelines are provided for writing SIAs for educational purposes in other contexts.